You know you love me : a Gossip Girl novel - Von Ziegesar, Cecily (New York : Little, Brown, 2002)
Blair and Serena, who go to an exclusive private school in Manhattan, are no longer best friends but are still both consumed with thoughts of boyfriends and college.
Young Adult.
Young Adult
Keywords: High schools -- Fiction; Man-woman relationships -- Fiction; Schools -- Fiction; High schools -- Fiction; Man-woman relationship -- Fiction; School stories; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction